Implementation of surveillance scheme in Health System by endemic levels or ranges in emergency department. - Luis Pedro Hernández Sosa; Sonia Pérez García; Juan José Apolinaire Pennini; Maira Valladares Vilches (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2008)
Background: Surveillance in health system is the follow up, data systematic collection, analysis and interpretation of health events to be used in planning, implementation and assessment of programs. Emergency department is a core place within an institution´s system and requires clear and timely information, statistical analysis and a constant and computerized surveillance system for appropriate decision making. Objective: To enforce a health surveillance system in emergency department through endemic levels or ranges. Methods: Descriptive research of chronological series developed in the emergency department of the University Paediatric Hospital in Cienfuegos. Data from chronological series from 2002 to 2006 was collected for 4 events. An automatic program was used to make the endemic levels or ranges. Conclusions: In this research, a surveillance system was presented with the elaboration of endemic levels or ranges of 4 events. This constitutes a useful, strong and accessible tool for the decision making process of the Directive Board.